2013
DOI: 10.1152/ajprenal.00669.2011
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 binding protein therapy is protective in adriamycin nephropathy

Abstract: Adriamycin nephropathy (AN) is an experimental model of focal segmental glomerulosclerosis (FSGS) in which macrophages are considered to play a pathogenic role. We hypothesize that interleukin-18 (IL-18), largely derived from macrophages, is a key contributor to kidney injury in AN and a potential therapeutic target. In this study, BALB/c mice received adriamycin (9.6 mg/kg) via tail vein injection and subsequently were treated with either neutralizing IL-18 binding protein (IL-18BP; 250 μg) or normal saline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Renal mononuclear leukocyte infiltration is seen in renal tissues of FSGS mice [16,17,50-52]. As shown in Figure 6A, although significantly increased renal peri-glomerular infiltration of T cells (CD3 + ) was seen at days 14 and 28 in FSGS+vehicle mice compared to normal control mice (both p < 0.005), this effect was markedly inhibited in FSGS+Citral mice (both p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Renal mononuclear leukocyte infiltration is seen in renal tissues of FSGS mice [16,17,50-52]. As shown in Figure 6A, although significantly increased renal peri-glomerular infiltration of T cells (CD3 + ) was seen at days 14 and 28 in FSGS+vehicle mice compared to normal control mice (both p < 0.005), this effect was markedly inhibited in FSGS+Citral mice (both p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study also indicated that, when administered at a dose previously used by Wyburn et al . () just before the first irinotecan injection, IL‐18bp protected against all of the intestinal injury‐related parameters examined, resulting in significant reductions in inflammatory reactions. It is also important to emphasize that we did not find any strain‐related differences in susceptibility to the development of intestinal mucositis between C57BL/6 and BALB/c mice, for any of the parameters studied.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of glomerulosclerosis was defined by the presence of PAS-positive staining material involving >30% of each glomerulus. Eighty to one-hundred glomeruli per animal from random, non-overlapping cortical regions were scored to determine the percentage of glomeruli displaying glomerulosclerosis [21]. Interstitial fibrosis was quantified by point counting of the trichrome-stained interstitium and expressed as a percentage of the total cortical area [22].…”
Section: Methodsmentioning
confidence: 99%